Project-based Collaborative Learning for Making Tie-dye to Improve the Skills of Vocational High School Students - Widihastuti, Widihastuti; Istanti, Hanifah Nur; Putri, Gina Eka; Dewi, Anita Volintia; Fitrihana, Noor; Kamis, Arasinah (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2023)
Developing the world of creative industries requires humane and creative human resources (HR). Educational institutions have a strategic role in developing creative human resources through learning that facilitates students to be active, wise, and collaborative. Therefore, it is necessary to implement project-based collaborative learning in learning activities, especially learning competencies related to the creative industry; one is about dyeing cloth with the popular tie-dye technique. This study was conducted at SMK N 1 Pengasih in the Fashion Design expertise program, using a project-based collaborative learning direct learning approach. The steps are; need assessment, learning preparation, tool and material preparation, learning implementation, and evaluation. The learning activity was declared successful because the number of targets present reached 100% with an activity level of 90%. The level of participation or activity in the learning process is grouped in the high category, namely 80%. This activity has a good impact and benefits students if the score is 80%. The evaluation design for increasing knowledge and skills was determined by the service team, as seen from the results of the tie-dye shirt product, with a score of 80% in the "good" category.